2013
DOI: 10.1111/jan.12301
|View full text |Cite
|
Sign up to set email alerts
|

Pain: A quality of care issue during patients' admission to hospital

Abstract: Reducing the risk of long-term persistent pain should be seen as integral to improving patient safety and can be achieved by harnessing organizational pain management processes with quality improvement initiatives. The assessment of pain alongside vital signs should be reviewed. Setting quality targets for pain are essential for improving the patient's experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
3
40
0
Order By: Relevance
“…A previous study supported this finding described that a pain management standard is effective for improving the quality of pain reduction, while an absence of standard results in inadequate pain management. [31] Similar findings have been found in previous studies in trauma. [3,20,21] This present study found that the hospitalized trauma patients rated moderate to high levels of satisfaction with the pain management strategies implemented by both the physicians and the nurses when they had pain at mild to moderate level during three days after admission.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study supported this finding described that a pain management standard is effective for improving the quality of pain reduction, while an absence of standard results in inadequate pain management. [31] Similar findings have been found in previous studies in trauma. [3,20,21] This present study found that the hospitalized trauma patients rated moderate to high levels of satisfaction with the pain management strategies implemented by both the physicians and the nurses when they had pain at mild to moderate level during three days after admission.…”
Section: Discussionsupporting
confidence: 82%
“…pain ratings), this is possible without the need for healthcare professionals to ask patients to complete a lengthy questionnaire. However, pain is shown to be requested and recorded at specific times and not tailored to patients’ needs (Carr et al., ). This implies that in addition to asking about pain intensity at regular intervals, pain assessments must be performed more frequently following breakthrough pain.…”
Section: Discussionmentioning
confidence: 99%
“…Carr et al. () consider pain assessments as a patient safety issue since high pain intensity after surgery may cause chronic pain. Although there can be difficulties in obtaining pain ratings, there are numerous benefits to optimizing pain assessments and documenting them.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies internationally have identified that pain is often substantially undertreated or untreated in geriatric patients (Daoust et al, 2014, Lukas et al, 2013, Morrison and Siu, 2000, Niruban et al, 2010, and that people with dementia are significantly less likely to receive analgesia than their cognitively intact counterparts (Closs et al, 2004, Hoffman et al, 2014, Morrison and Siu, 2000. There are particular issues with the management of pain for older patients in acute hospital settings (Atkinson and Almahdi, 2014, Carr et al, 2014, Chang et al, 2010, Lin et al, 2014, Niruban et al, 2010. Poor management of pain may lead to slower rehabilitation and a decrease in physical function with hospitals stays longer for a person with dementia than for others admitted for the same procedure (Alzheimer's Society,…”
Section: Introductionmentioning
confidence: 99%